The very faint X-ray binary IGR J17062-6143: a truncated disc, no pulsations, and a possible outflow. Issue 2 (15th December 2017) - van den Eijnden, J; Degenaar, N; Pinto, C; Patruno, A; Wette, K; Messenger, C; Hernández Santisteban, J V; Wijnands, R; Miller, J M; Altamirano, D; Paerels, F; Chakrabarty, D; et al.
Abstract: We present a comprehensive X-ray study of the neutron star low-mass X-ray binary IGR J17062-6143, which has been accreting at low luminosities since its discovery in 2006. Analysing NuSTAR, XMM–Newton, and Swift observations, we investigate the very faint nature of this source through three approaches: modelling the relativistic reflection spectrum to constrain the accretion geometry, performing high-resolution X-ray spectroscopy to search for an outflow, and searching for the recently reported millisecond X-ray pulsations. We find a strongly truncated accretion disc at $77^{+22}_{-18}$ gravitational radii (∼164 km) assuming a high inclination, although a low inclination and a disc extending to the neutron star cannot be excluded. The high-resolution spectroscopy reveals evidence for oxygen-rich circumbinary material, possibly resulting from a blueshifted, collisionally ionized outflow. Finally, we do not detect any pulsations. We discuss these results in the broader context of possible explanations for the persistent faint nature of weakly accreting neutron stars. The results are consistent with both an ultra-compact binary orbit and a magnetically truncated accretion flow, although both cannot be unambiguously inferred. We also discuss the nature of the donor star and conclude that it is likely a CO or O–Ne–Mg white dwarf, consistent with recent multiwavelength modelling.